Case Report: Diffuse Large B Cell Lymphoma After Cardiac Transplantation due to Anthracycline-Induced Dilated Cardiomyopathy in Pediatric Acute Lymphoblastic Leukemia - Xin, Ning; Chunyan, Cao; You, Zhou; Lu, Peng; Runming, Jin; Fen, Zhou (Frontiers in Pharmacology, 2022)
Anthracycline is a first-line chemotherapy drug used to treat childhood acute leukaemia, which may cause cardiac toxicity including common arrhythmia, valve disease, pericardial effusion, and even rare cardiomyopathy and cardiac failure. We reported a 2-year-old boy who was treated irregularly for acute lymphoblastic leukaemia with daunorubicin. After 26 months, his left ventricular ejection fraction decreased to 40% and progressively decreased to 20%-30%. Then he successfully received heart transplantation and the myocardium was confirmed with dilated cardiomyopathy. Eight months after cardiac transplantation, he was admitted again for left neck mass and was diagnosed with monomorphic diffuse large B cell lymphoma associated with Epstein-Barr virus infection by biopsy. We present this case to highlight the importance of standard chemotherapy of daunorubicin, clinical prevention and monitoring of anthracycline-induced cardiotoxicity in acute lymphoblastic leukaemia children, to ensure their good prognosis and long-term life quality.